1996
DOI: 10.1073/pnas.93.22.12637
|View full text |Cite
|
Sign up to set email alerts
|

Higher plants contain homologs of the bacterial celA genes encoding the catalytic subunit of cellulose synthase.

Abstract: In spite of much effort, no one has succeeded in isolating and characterizing the enzyme(s) responsible for synthesis of cellulose, the major cell wall polymer of plants. We have characterized two cotton (Gossypium hirsutum) cDNA clones and identified one rice (Oryza sativa) cDNA that are

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
526
0
6

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 658 publications
(556 citation statements)
references
References 30 publications
(35 reference statements)
15
526
0
6
Order By: Relevance
“…Besides, sequence analysis revealed existence of the motif D, D, D, QxxRW (motifs indicative of processive glycosyltransferase) (Saxena and Brown, 1995). It was shown that GhCESA1 was able to bind to the substrate UDP-glucose and the expression patterns of GhCesA1 and GhCesA2 were tightly linked with the timing of cellulose biosynthesis (Pear et al, 1996). Collectively, these findings supported the hypothesis that GhCesA1 and GhCesA2 encoded potential catalytic subunits of CelS which may be associated with biogenesis of microfibrils of cellulose .…”
Section: Cels Is Composed Of Cesa Isoforms That Are Encoded By Cesa Gsupporting
confidence: 73%
See 4 more Smart Citations
“…Besides, sequence analysis revealed existence of the motif D, D, D, QxxRW (motifs indicative of processive glycosyltransferase) (Saxena and Brown, 1995). It was shown that GhCESA1 was able to bind to the substrate UDP-glucose and the expression patterns of GhCesA1 and GhCesA2 were tightly linked with the timing of cellulose biosynthesis (Pear et al, 1996). Collectively, these findings supported the hypothesis that GhCesA1 and GhCesA2 encoded potential catalytic subunits of CelS which may be associated with biogenesis of microfibrils of cellulose .…”
Section: Cels Is Composed Of Cesa Isoforms That Are Encoded By Cesa Gsupporting
confidence: 73%
“…The identification of potential components of the plant CelS complex was achieved by a molecular approach. Two cDNA clones GhCESA1 and GhCESA2 were identified in cotton fiber enriched in cellulose (Pear et al, 1996). These cDNAs encoded proteins with some similarity to the bacterial CESA proteins.…”
Section: Cels Is Composed Of Cesa Isoforms That Are Encoded By Cesa Gmentioning
confidence: 99%
See 3 more Smart Citations